Management Options and Factors Affecting Control of a Common Waterhemp (Amaranthus rudis) Biotype Resistant to Protoporphyrinogen Oxidase-Inhibiting Herbicides - Dana B. Harder; Kelly A. Nelson; Reid J. Smeda (International Journal of Agronomy)
Repeated use of protox-inhibiting herbicides has resulted in a common waterhemp (Amaranthus rudis Sauer) biotype that survived lactofen applied up to 10 times the labeled rate. Field and greenhouse research evaluated control options for this biotype of common waterhemp. In the field, PRE applications of flumioxazin at 72 g ai ha−1, sulfentrazone at 240 g ai ha−1, and isoxaflutole at 70 g ai ha−1 controlled common waterhemp >90% up to 6 weeks after treatment. POST applications of fomesafen at 330 g ai ha−1, lactofen at 220 g ai ha−1, and acifluorfen at 420 g ai ha−1 resulted in <60% visual control of common waterhemp, but differences were detected among herbicides. In the greenhouse, glyphosate was the only herbicide that controlled protox resistant waterhemp. The majority of herbicide activity from POST flumioxazin, fomesafen, acifluorfen, and lactofen was from foliar placement, but control was less than 40% regardless of placement. Control of common waterhemp seeded at weekly intervals after herbicide treatment with flumioxazin, fomesafen, sulfentrazone, atrazine, and isoxaflutole exceeded 85% at 0 weeks after herbicide application (WAHA), while control with isoxaflutole was greater than 60% 6 WAHA. PRE and POST options for protox-resistant common waterhemp are available to manage herbicide resistance.